2019
DOI: 10.1063/1.5114249
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate counting: How accurate should it be to achieve glycemic control in patients on intensive insulin regimens?

Abstract: Carbohydrate counting is an important meal-planning tool for patients on intensive insulin regimens. Preprandial insulin bolus is adjusted taking into account the carbohydrate content of each meal and the insulin-to-carb ratio of each patient throughout the day. Evidence suggests that accurate carbohydrate counting may have positive effects not only on reducing glycosylated hemoglobin concentration but also on decreasing the incidence of hypoglycemic episodes. Nevertheless, despite its benefits, the efficacy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…In this context, we proposed an analytic method that uses patient-specific data to compute the safe maximum interval for the error of the insulin-to-carbohydrate ratio estimations. Moreover, our method could be used to quantify the impact of lifestyle changes on patient health, 1 By AIM system, we can consider that the insulin-to-carbohydrate ratio does not change when the bodyweight changes, because the Total Daily Dose (T DD) insulin is linearly dependent of bodyweight. In AIM system is considered that T DD = k 1 • W, where k 1 is a nonzero positive constant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, we proposed an analytic method that uses patient-specific data to compute the safe maximum interval for the error of the insulin-to-carbohydrate ratio estimations. Moreover, our method could be used to quantify the impact of lifestyle changes on patient health, 1 By AIM system, we can consider that the insulin-to-carbohydrate ratio does not change when the bodyweight changes, because the Total Daily Dose (T DD) insulin is linearly dependent of bodyweight. In AIM system is considered that T DD = k 1 • W, where k 1 is a nonzero positive constant.…”
Section: Discussionmentioning
confidence: 99%
“…Under these circumstances, the proposed method suggests that patients may experience some benefits if they have a bodyweight gain 1 . Nevertheless, it's important to bear in mind that diet to increase bodyweight must not increment the carbohydrates intake per meal.…”
Section: ) Patients With Low Bodyweight For Heightmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies attempted to quantify the impact of carbcounting error on T1D patients glycemic control, showing that CHO underestimation can cause postprandial hyperglycemia, while CHO overestimation can lead to hypoglycemic episodes. [16][17][18][19][20] Moreover, Smart et al 21 found that an error of ±10g per meal or snack on a meal size of 60g did not significantly deteriorate the postprandial control, while a ±20g error had a significant impact on postprandial glycemia. 22 Although errors in carb-counting can be mitigated by the adoption of closed-loop insulin delivery systems, 23 these systems are still used by only a fraction of people with T1D.…”
Section: Introductionmentioning
confidence: 99%
“…However, to be effective, the bolus insulin dose must be accurate. Although, to correctly calculating it is not simple since it depends on several factors, i.e., the carbohydrate intake at each meal (CHO) [2,3], the Insulin to Carbohydrate Ratio (ICR), the Insulin Sensitivity Factor (IS F), the preprandial blood glucose [4], the postprandial blood glucose target and the insulin remaining active from the last boluses. Concerning the ICR and IS F factors, they are correlated and dynamic [5][6][7], changing along the day due to several factors, namely, physical activity, stress, health condition, or the hormone cycle, making it hard to get [8].…”
Section: Introductionmentioning
confidence: 99%